Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2018)
A dataset containing 30265 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Acorus calamus L.", "HasCoordinate is TRUE", "HasGeospatialIssue is FALSE" ] } The dataset includes 30265 records from 226 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0035430-180508205500799/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences